Predictors of hospitalisations and emergency department presentations shortly after entering a residential aged care facility in Australia: a retrospective cohort study. Issue 11 (17th November 2021) - Inacio, Maria C; Jorissen, Robert N; Wesselingh, Steve; Sluggett, Janet K; Whitehead, Craig; Maddison, John; Forward, John; Bourke, Alice; Harvey, Gillian; Crotty, Maria
Abstract : Objectives: To: (1) examine the 90-day incidence of unplanned hospitalisation and emergency department (ED) presentations after residential aged care facility (RACF) entry, (2) examine individual-related, facility-related, medication-related, system-related and healthcare-related predictors of these outcomes and (3) create individual risk profiles. Design: Retrospective cohort study using the Registry of Senior Australians. Fine-Gray models estimated subdistribution HRs and 95% CIs. Harrell's C-index assessed risk models' predictive ability. Setting and participants: Individuals aged ≥65 years old entering a RACF as permanent residents in three Australian states between 1 January 2013 and 31 December 2016 (N=116 192 individuals in 1967 RACFs). Predictors examined: Individual-related, facility-related, medication-related, system and healthcare-related predictors ascertained at assessments or within 90 days, 6 months or 1 year prior to RACF entry. Outcome measures: 90-day unplanned hospitalisation and ED presentation post-RACF entry. Results: The cohort median age was 85 years old (IQR 80–89), 62% (N=71 861) were women, and 50.5% (N=58 714) had dementia. The 90-day incidence of unplanned hospitalisations was 18.0% (N=20 919) and 22.6% (N=26 242) had ED presentations. There were 34 predictors of unplanned hospitalisations and 34 predictors of ED presentations identified, 27 common to both outcomes and 7 were unique to each. The hospitalisation and ED presentation models out-of-sample Harrell's C-index was 0.664 (95% CI 0.657 to 0.672) and 0.655 (95% CI 0.648 to 0.662), respectively. Some common predictors of high risk of unplanned hospitalisation and ED presentations included: being a man, age, delirium history, higher activity of daily living, behavioural and complex care needs, as well as history, number and recency of healthcare use (including hospital, general practitioners attendances), experience of a high sedative load and several medications. Conclusions: Within 90 days of RACF entry, 18.0% of individuals had unplanned hospitalisations and 22.6% had ED presentations. Several predictors, including modifiable factors, were identified at the time of care entry. This is an actionable period for targeting individuals at risk of hospitalisations.